The Dilemma of Internal Control System (SPI) Compliance Requirements and Profitability Pressures - Baihaqi Ahmad, Imam; Asyik, Nur Fadjrih (E-Jurnal Akuntansi, 2026)
This study aims to understand how management interprets the dilemma between Internal Control System (SPI) compliance and profitability pressure and its implications for decision-making. The study was conducted at PT KAI, a plywood manufacturing company in East Java, using a qualitative phenomenological approach. Data were collected through in-depth interviews with the Director and FAT Manager, supported by observation and documentation. The analysis used thematic analysis to identify and interpret meaning. The findings show that SPI is interpreted ambivalently, as a risk control mechanism and as an operational burden. Profitability pressure is interpreted as a key consideration, leading to selective SPI implementation based on risk and operational needs. This study contributes by showing that SPI implementation is shaped by managerial meaning-making in navigating the tension between compliance and profitability.